Developing Psychometric Property Measuring Equipment Readiness for Employees Retirement - Angela, Grace; Fajrianthi, Fajrianthi; Syarifah, Dewi; Rahmadhani, Inastuti (Budapest International Research and Critics University, 2022)
Retirement is considered a worrying time, especially for employees who are not mentally prepared. This study aims to develop a retirement preparation scale based on a psychometric approach. The survey design used a correlation approach with the survey data collection method. Respondents are PT. Pembangkitan Jawa Bali employees (N = 57). The retirement scale includes five aspects: physical, mental, financial, performance, and health assessment. The retirement readiness scale has 27 points. This study can be divided into two scenarios: Aikens V for Phase 1 tests and Properties for Phase 2 tests. The psychological analysis includes reliability of internal coherence (Alpha Cronach) and validity of constructs (convergence discriminant). Use the correlation between items to test the reliability of the measure. Use confirmatory factor analysis to test the effectiveness of the instrument. Analysis of the psychometric properties of the device that measures retirement readiness resulted in an Alpha reliability of 0.91. The result of this survey is a retirement motivation measure created using field data. The PT. Pembangkitan Jawa Bali employee's retirement motivation measuring instrument consists of 17 items, 2 of which are unanswered questions and 15 of which are for measuring retirement motivation. Most PT. Pembangkitan Jawa Bali employee retirement readiness scale findings can be transferred to other public companies.